Bharat`s indirect taxation - Rafi, Mohd. (New Delhi, 2017)
The focus of this edition is to facilitate easy learning by the student community, taking into account the paucity of time at their disposal. Tax professionals and businesses may also find the book very useful.
Keywords: Law